2015
DOI: 10.1016/j.neuroimage.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Edge density imaging: Mapping the anatomic embedding of the structural connectome within the white matter of the human brain

Abstract: The structural connectome has emerged as a powerful tool to characterize the network architecture of the human brain and shows great potential for generating important new biomarkers for neurologic and psychiatric disorders. The edges of the cerebral graph traverse white matter to interconnect cortical and subcortical nodes, although the anatomic embedding of these edges is generally overlooked in the literature. Mapping the paths of the connectome edges could elucidate the relative importance of individual wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 56 publications
4
62
0
Order By: Relevance
“…In the plots, each point represents the mean relative difference (RD) of FA versus the mean parcel volume across all subjects in one dataset. A low relative difference value represents a high test-retest reproducibility [Color figure can be viewed at wileyonlinelibrary.com] Ciccarelli et al, 2003;Cousineau et al, 2017;Duan et al, 2015;Kristo et al, 2013;Lin et al, 2013;Owen et al, 2015;Papinutto et al, 2013;Pfefferbaum et al, 2003;Smith et al, 2015;Vollmar et al, 2010;Wang et al, 2012;Yendiki et al, 2016;Zhao et al, 2015), one study performed volumetric-overlap-based experiments in a comparable way to the present study (Cousineau et al, 2017) Volumetric overlap of anatomical fiber tracts identified from the test-retest dMRI data using the fiber clustering (FC) and corticalparcellation-based (CPB) methods. Plots show the mean wDice score (averaged across subjects in each dataset) for each tract.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the plots, each point represents the mean relative difference (RD) of FA versus the mean parcel volume across all subjects in one dataset. A low relative difference value represents a high test-retest reproducibility [Color figure can be viewed at wileyonlinelibrary.com] Ciccarelli et al, 2003;Cousineau et al, 2017;Duan et al, 2015;Kristo et al, 2013;Lin et al, 2013;Owen et al, 2015;Papinutto et al, 2013;Pfefferbaum et al, 2003;Smith et al, 2015;Vollmar et al, 2010;Wang et al, 2012;Yendiki et al, 2016;Zhao et al, 2015), one study performed volumetric-overlap-based experiments in a comparable way to the present study (Cousineau et al, 2017) Volumetric overlap of anatomical fiber tracts identified from the test-retest dMRI data using the fiber clustering (FC) and corticalparcellation-based (CPB) methods. Plots show the mean wDice score (averaged across subjects in each dataset) for each tract.…”
Section: Discussionmentioning
confidence: 84%
“…In comparison to related work on test–retest reproducibility of white matter parcellation, we found that both of the fiber clustering and cortical‐parcellation‐based methods performed relatively well. While existing studies applied different evaluation criteria using different testing datasets (Besseling et al, ; Cheng et al, ; Ciccarelli et al, ; Cousineau et al, ; Duan et al, ; Kristo et al, ; Lin et al, ; Owen et al, ; Papinutto et al, ; Pfefferbaum et al, ; Smith et al, ; Vollmar et al, ; Wang et al, ; Yendiki et al, ; Zhao et al, ), one study performed volumetric‐overlap‐based experiments in a comparable way to the present study (Cousineau et al, ). In this work, Cousineau et al studied test–retest reproducibility of a Freesurfer‐based cortical‐parcellation‐based anatomical tract parcellation on PPMI data and suggested a threshold for a good wDice score to be 0.72 (based on an analysis of the mean wDice score across data in a healthy population; Cousineau et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), affecting among others the long association fibres, and the most common sites of lacunes (among others) are the basal ganglia and thalamus [Benjamin et al, ]. These regions are commonly found to be involved in the rich club organisation in structural networks [Owen et al, ] and thus damage to these regions or white matter tracts among these regions may produce disproportionate disturbance in the rich club organisation. Although the number of rich club connections is small, the widespread nature of white matter damage in SVD may have a greater overall impact on these connections due to the spatial embedding of the connections.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior network-analytic work has largely focused on cortico-cortical topologypossibly in part due to technical limitations inherent in studying connectivity of subcortical nuclei (see Section 3.2.1)recent examples in the literature have incorporated subcortical nodes into their analysis of rich-club patterning in human structural tractography data (van den Heuvel and Sporns, 2011;McColgan et al, 2015;Owen et al, 2015). Results from these studies reveal that the striatum and thalamus form part of the neural "rich-club" (van den Heuvel and Sporns, 2011;McColgan et al, 2015;Owen et al, 2015) and are in-line with findings from tract-tracing work in Macaque monkeys demonstrating that striatal and thalamic nuclei belong to an integrated core circuit (Modha and Singh, 2010) (Figure 1c).…”
Section: Subcortical Hubs: 'Rich' Contributions To Large-scale Integrmentioning
confidence: 99%